Media and Technology in Emerging African Democracies - Nwokeafor, Cosmas Uchenna; Langmia, Kehbuma (Hamilton Books, 2010)
Media and Technology in Emerging African Democracies is a standard text that will give students an opportunity to familiarize themselves with some of the best literature in media technology impact in emerging African democracies with relevant concentration on information and communication technology (ICT). This textbook is a collection of essays that may be used as primary reading for courses on mass media technology, and information communication technology (ICT). It is also suitable as supplementary reading in media and politics, political science and courses that focus on political communication, and business communication. The book serves as a reference guide to mass media scholars, development communication experts, government leaders, and diplomats interested in media review, most importantly as it pertains to African democratic dispensations. The book includes contributions by scholars whose research interests in media and its relevant impact on African democratic system have stirred considerable academic discourse. The chapters span several social science disciplines, giving students, professionals, and government agencies an opportunity to see challenges from an interdisciplinary perspective.